An insight into the relationships between hepcidin, anemia, infections and inflammatory cytokines in pediatric refugees: a cross-sectional study. - Sarah Cherian (Public Library of Science (PLoS), 2008)
Background Hepcidin, a key regulator of iron homeostasis, is increased in response to inflammation and some infections, but the in vivo role of hepcidin, particularly in children with iron deficiency anemia (IDA) is unclear. We investigated the relationships between hepcidin, cytokines and iron status in a pediatric population with a high prevalence of both anemia and co-morbid infections. Methodology/principal findings African refugee children <16 years were consecutively recruited at the initial post-resettlement health check with 181 children meeting inclusion criteria. Data on hematological parameters, cytokine levels and co-morbid infections (Helicobacter pylori, helminth and malaria) were obtained and urinary hepcidin assays performed. The primary outcome measure was urinary hepcidin levels in children with and without iron deficiency (ID) and/or ID anaemia (IDA). The secondary outcome measures included were the relationship between co-morbid infections and (i) ID and IDA, (ii) urinary hepcidin levels and (iii) cytokine levels. IDA was present in 25/181 (13.8%). Children with IDA had significantly lower hepcidin levels (IDA median hepcidin 0.14 nmol/mmol Cr (interquartile range 0.05-0.061) versus non-IDA 2.96 nmol/mmol Cr, (IQR 0.95-6.72), p<0.001). Hemoglobin, log-ferritin, iron, mean cell volume (MCV) and transferrin saturation were positively associated with log-hepcidin levels (log-ferritin beta coefficient (beta): 1.30, 95% CI 1.02 to 1.57) and transferrin was inversely associated (beta: -0.12, 95% CI -0.15 to -0.08). Cytokine levels (including IL-6) and co-morbid infections were not associated with IDA or hepcidin levels. Conclusions/significance This is the largest pediatric study of the in vivo associations between hepcidin, iron status and cytokines. Gastro-intestinal infections (H. pylori and helminths) did not elevate urinary hepcidin or IL-6 levels in refugee children, nor were they associated with IDA. Longitudinal and mechanistic studies of IDA will further elucidate the role of hepcidin in paediatric iron regulation.